KOMPETENSI PROFESIONAL GURU DALAM MENINGKATKAN PEMBELAJARAN SKI BERBASIS TEKNOLOGI DI MADRASAH IBDTIDAIYAH KONDANGJAYA - Hayati, Ela Hikmah (Ta'dibiya, 2023)
This study discusses Teacher Professional Competence in Improving Technology-Based SKI Learning at Madrasah Ibdtidaiyah Kondangjaya. With the aim of describing and analyzing factors inhibiting teacher competence in improving SKI learning at the Kondangjaya Ibdtidaiyah madrasah. The approach used is a qualitative-descriptive approach. The method used in this research uses literature and field study methods. The results of this research show that teachers' professional competence cannot improve SKI learning at the Kondangjaya Ibdtidaiyah madrasah due to the lack of supporting factors from school principals such as holding training and attending educational seminars that can develop teacher competence in the teaching process. Another factor is human resources which hinder teachers from developing. Keywords: Teacher Professional Competence, History of Islamic Culture, technology